Survey on physician attitudes and knowledge toward colorectal cancer screening in primary health care centers, Qassim, Saudi Arabia - Aljemeeli, Feras A.; Alfadda, Abdulrahman (International Journal of Advances in Medicine, 2022)
Background: Colorectal cancer (CRC) is one of the leading causes of cancer incidence worldwide. In Saudi Arabia, it is ranked first most common cancer in males and second most common in females. CRC is an ideal for prevention because of the high incidence rate and the relative slow progression into an adenocarcinoma. Primary health care (PHC) setting is the ideal place where CRC screening should take place. This study was intended to evaluate awareness, knowledge and attitude towards CRC screening. Methods: A survey was performed among PHC physicians in Qassim province, Saudi Arabia. An electronic questionnaire adopted from the national cancer institute was formulated. Demographic data, specialty, qualifications, years of experience, knowledge and attitudes towards CRC screening, and perceived barriers regarding CRC screening were obtained. Results: A total of 94 physicians were recruited. 39.4% from the sample are females, and 60.6% are males. 99% of physicians agree that colorectal cancer screening is needed when age appropriate. However, 68% were very compliant in CRC screening in clinical practice. Only 52% of physicians were familiar with national CRC cancer screening guidelines. 53% of physicians scored correct on the age appropriate to initiate CRC screening for average risk patients. Conclusions: More efforts should be given to improve knowledge of primary healthcare providers regarding CRC prevention. More funding and planning are needed to provide primary health care providers with the required tools and systems in order to make CRC prevention more efficient.